Chad : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper analyzes economic developments in Chad during 1990-98. Chad resumed its economic adjustment efforts in 1994-95, in the aftermath of the devaluation of the CFA franc of 1994, and embarked, in mid-1995, on a comprehensive structural adjustment program. During the period 1994-98, significant economic progress was made in Chad, with the implementation of economic and financial reforms and enhancement of the policy environment. As a result, macroeconomic performance improved markedly, and the economy's domestic and external imbalances were reduced.